Factors influencing adherence to oral nutritional supplementation in patients with gastrointestinal neoplasms: a mixed methods systematic review - Lin, Yanni; Fan, Siyue; Chai, Wenting; Zheng, Nengtong; Yu, Doudou; Yang, Liping; Chen, Lijuan (Supportive care in cancer, 2025)
Objective To explore specific determinants influencing oral nutritional supplementation (ONS) adherence in gastrointestinal neoplasm patients. Methods This PROSPERO-registered (CRD42024611358) systematic review followed PRISMA 2020 guidelines. Databases including PubMed, Web of Science, and CNKI were searched from inception to April 2025. Included studies underwent quality appraisal and integrative analysis using JBI mixed-methods guidelines. Results A total of 14 original studies were included, comprising 9 quantitative studies, 2 qualitative studies, and 3 mixed-methods studies, involving 1874 gastrointestinal neoplasm patients (1779 in quantitative studies and 95 in qualitative studies). Among the 9 quantitative studies, 1 was a discrete choice experiment. Through analysis, 29 influencing factors were identified, such as perceived benefits, educational level, family caregiver support, economic status, healthcare providers, palatability, adverse reactions, side effects of cancer treatments, and tumor types. These factors were categorized into 9 categories and mapped to the five dimensions of adherence proposed by the World Health Organization. Using a systematic prioritization framework (based on evidence strength, frequency of identification in original studies, and clinical intervenability), three critical determinants emerged as the most impactful: adverse reactions (confirmed by 10 original studies, including 6 high-quality studies), side effects of cancer treatments (supported by 7 original studies, with 5 high-quality studies), and perceived benefits (recognized by 6 original studies, including 5 high-quality studies). Conclusions ONS adherence is affected by multiple specific factors, with adverse reactions, cancer treatment side effects, and perceived benefits as critical priorities. Interventions should include symptom management for adverse reactions, supportive care for treatment side effects, standardized nutrition education to enhance perceived benefits, and personalized adjustments for palatability. These recommendations guide targeted clinical interventions and future research on improving ONS adherence.